Factors Influencing the Usage of Compact Fluorescent Lamps in Existing Residential Buildings in Lagos, Nigeria - Johnson, Olusola Olugbemileke; Odekoya, Abayomi Joseph; Umeh, Obinna Lawrence (International Journal of Energy Economics and Policy, 2012)
Nigeria as a developing nation is facing increasing demand for electricity especially in the residential areas. The use of compact fluorescent lamps (CFLs) is one of the several measures towards reducing the demand. However, in Nigeria, the use of CFLs is low. The present study was designed to investigate some factors responsible for the low usage of CFLs in Lagos, Nigeria. Questionnaires were administered by hand on 984 households, selected through systematic random sampling techniques from 5 local government areas in Lagos State. The first building along the major street in each of the local government was selected randomly and every tenth building constituted the sample. A household head was surveyed in each of the building selected, and was asked to rate some factors that might have influenced the usage of CFLs. The data generated from the questionnaire were analysed using ranking method. The findings show that inability to measure the saving benefits of CFLs on electricity bills, lack of affordability and high initial cost of acquisition and installation were the most important factors which influence the use of the CFLs. The study concludes by providing some recommendations on how to achieve sustainable energy management in the Lagos and beyond through more efficient residential house lighting. Keywords: Electricity; Energy usage; Energy Efficiency; Incandescent Bulbs; Compact Fluorescent Lamps JEL Classification: Q